Conceptual basis of the criteria of species on the example of aphids (Homoptera, Aphididae, Pemphigidae) - Fedorenko, V. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2017)
The conception of species and speciation criteria for the example of Aphididae and Pemphigidae aphids is shown, which is of theoretical and practical importance for understanding homeostatic mechanisms of formation of adaptive populations in order to improve protective measures against harmful insects.